We're back! : a dinosaur's story [videorecording (DVD)] - Spielberg, Steven, 1946-; Zondag, Dick; Zondag, Ralph; Nibbelink, Phil; Wells, Simon; Shanley, John Patrick; Goodman, John, 1952-; Perlman, Rhea; Leno, Jay; LeVant, Rene; Kendal, Felicity; Fleischer, Charles; et al. (Universal Studios Home Entertainment, 2009)
The tale of four huge but huggable dinos who visit New York City to make millions of children's dreams come true. With his IQ-boosting 'Brain Grain' cereal, the time-traveling Captain New Eyes transforms Rex, Elsa, Dweeb, and Woog into thinking, feeling, talking creatures.